UPAYA IMPLEMENTASI NDC (NATIONALLY DETERMINED CONTRIBUTION) GUNA MENCAPAI KETAHANAN IKLIM (CLIMATE RESILIENCE) DI BIDANG PERTANIAN - Pembengo, Wawan; Dude, Suyono (Universitas Mataram, 2024)
In the Updated NDC (UNDC) document, Indonesia's GHG emission reduction target with its own capabilities of 29% increased to 31.89%, while the target with international support of 41% increased to 43.20%. The climate resilience of the agricultural sector is very important where food security, economic and ecological stability and sustainable development are greatly threatened by climate irregularities. Technological innovation in agricultural activity models by considering location-specific aspects by combining various aspects so that they can further increase optimal carbon absorption is an understanding of carbon efficient agricultural technology. The aim of the service activities is to build capacity and participation at the farmer level through carbon efficient agricultural technology programs in the context of efforts to implement NDC to achieve climate resilience in the agricultural sector. The implementation of collaborative service activities in nggulo village, Tilongkabila District, Bone Bolango Regency will take place from May to June 2023. The number of students involved is 10 from the Agrotechnology study program, Faculty of Agriculture, Gorontalo State University. The method used in this collaborative service activity is participatory training with activities in the form of counseling and technical guidance. The form of program implemented includes a carbon efficient agricultural technology program including agricultural land optimization activities in the form of increasing the cropping index through the jajar legowo technique and biopesticide techniques. Land management in the form of biopore techniques. The result of this activity is a carbon efficient agricultural technology program in the form of the jajar legowo technique which can be implemented by farmers which is applied to tomato and land kale plants using the jajar legowo technique 2 : 1 and 3 : 1. The jajar legowo system is applied by planting with a pattern of several rows of plants interspersed one empty row as legowo which has the function of being a space for plant management in the form of weeding, irrigation and HPT control activities. In biopesticide activities, soursop extraction can be used as an organic insecticide. In biopore activities, this technique is not only used as water absorption, but also as soil fertilizer, reduces the accumulation of waste which causes various health problems and plays a role in maintaining soil water levels from the threat of drought. Based on the results of activities, the carbon efficient agricultural technology program can be one of the efforts to implement NDC at the site level through empowering farmers to build capacity and independent participation to achieve climate resilience in the agricultural sector.